A new species of anapid spider (Araneae: Araneoidea, Anapidae) in Eocene Baltic amber, imaged using phase contrast X-ray computed micro-tomography - Penney, David; Mcneil, Andrew; Green, David I.; Bradley, Robert; Marusik, Yuri M.; Withers, Philip J.; Preziosi, Richard F. (Zootaxa, 2011)
A new species of the extant spider family Anapidae is described from a fossil mature male in Eocene amber from the Baltic region and tentatively assigned to the genus Balticoroma Wunderlich, 2004. Phase contrast X-ray computed micro-tomography was used to reveal important features that were impossible to view using traditional microscopy. Balticoroma wheateri new species is easily diagnosed from all other anapids by having clypeal extensions that run parallel to the ectal surface of the chelicerae and in having the metatarsus of the first leg highly reduced and modified into what is presumably a y-shaped clasping structure. Although only a single extant anapid species occurs in northern Europe, the family was diverse in the Eocene. The discovery of yet another anapid species in Baltic amber supports the idea that Eocene European forests may have been a hotspot of evolution for this family of spiders.